Regulation of diurnal variation of cholesterol 7?-hydroxylase (CYP7A1) activity in healthy subjects - Kovář, Jan; Leníček, Martin; Zimolová, Miluše; Vítek, Libor; Jirsa, Milan; Piťha, Jan (Physiological research, 2010)
Cholesterol 7?-hydroxylase (CYP7A1), the key regulatory enzyme of bile acid synthesis, displays a pronounced diurnal variation. To better understand the regulation of CYP7A1 activity, three daylong examinations were carried out in 12 healthy men. The concentrations of 7?-hydroxycholest-4-en-3-one (C4), a surrogate marker of CYP7A1 activity, bile acids (BA), insulin, glucose, nonesterified fatty acids, triglycerides, and cholesterol were measured in serum in 90-min intervals from 7 AM till 10 PM. To lower and to increase BA concentration during the study, the subjects received cholestyramine and chenodeoxycholic acid (CDCA), respectively, in two examinations. No drug was used in the control examination. There was a pronounced diurnal variation of C4 concentration with a peak around 1 PM in most of the subjects. The area under the curve (AUC) of C4 concentration was five times higher and three times lower when subjects were treated with cholestyramine and CDCA, respectively. No relationship was found between AUC of C4 and AUC of BA concentration, but AUC of C4 correlated positively with that of insulin. Moreover, short-term treatment with cholestyramine resulted in about 10 % suppression of glycemia throughout the day. Our results suggest that insulin is involved in the regulation of diurnal variation of CYP7A1 activity in humans.
Keywords: Triglycerides; Fatty Acids, Nonesterified; Clinical Trials as Topic; Cholesterol; gastrointestinální látky; aktivace enzymů; Male; kyselina chenodeoxycholová; klinické zkoušky jako téma; krevní glukóza; Cholestenones; Enzyme Activation; Cholesterol 7-alpha-Hydroxylase; Reference Values; financování organizované; kyseliny mastné neesterifikované; Bile Acids and Salts; cirkadiánní rytmus; cholesterol-7-alfa-hydroxylasa; triglyceridy; inzulin; mužské pohlaví; Anticholesteremic Agents; Insulin; Adult; Financing, Organized; Circadian Rhythm; Chenodeoxycholic Acid; cholestyraminová pryskyřice; Blood Glucose; referenční hodnoty; Gastrointestinal Agents; cholesterol; anticholesteremika; cholestenony; dospělí; Cholestyramine Resin; žlučové kyseliny a soli; lidé; Humans